Effect of Infection with Toxoplasma and Cytomegalovirus on (IgG and IgM) Levels in Women with Primary Infertility from Wasit Province-Iraq - Hind A. Hanoon (Journal of Global Pharma Technology, 2019)
The purpose of this study is to clarify the respective roles of the parasite Toxoplasma and cytomegalovirus in primary infertility women in Wasit governorate, the samples were collected from each of infertility center at Al-Kut Hospital and Al-Zahra Teaching Hospital during the period from of 20may to 20 Oct. /2016. and was compared with the control groups Pregnant  and healthy women , it was the reconstruction of aggregates rate between 17- 45 years, and have been working with ELISA .this study showed  a significant decrease (P <0.05)  in IgM in  first and second  groups when compared with healthy women and no significant when compared with pregnant women at toxoplasmosis .In Cytomegalovirus, significant increase (P <0.05) for all categories compared with healthy in IgM  and significant increase (P <0.05) in first and third categories in IgG when compared with pregnant women and significant decrease (P <0.05) in second group in IgM when compared with pregnant women.Keywords: Toxoplasma gondii, Cytomegalovirus, Infertility women, Pregnant women, ELISA.